2008
DOI: 10.5007/2175-7925.2008v21n4p73
|View full text |Cite
|
Sign up to set email alerts
|

Densidade e distribuição espacial do caranguejo Ocypode quadrata (Fabricius, 1787) (Crustacea, Ocypodidae) em três praias arenosas do Espírito Santo, Brasil

Abstract: Submetido em 11/02/2008 Aceito para publicação em 25/06/2008Resumo A densidade relativa (n o de tocas/m 2 ) e a distribuição espacial do caranguejo Ocypode quadrata foram avaliadas em três praias arenosas do município de Vila Velha-ES: Itaparica, Itapoã e Praia da Costa. Nas três praias, as amostragens foram conduzidas nos dias 25/05, 13/06, 26/06 e 11/07/2006. Em cada dia, foram distribuídos aleatoriamente por praia, dois transectos de 5m de largura perpendiculares a linha d'água, divididos em retângulos de 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
8
0
7
Order By: Relevance
“…Changes in the morphological development of talitrid amphipods (T. saltator) have been associated with human impacts. On the coast of Spain, Barca-Bravo et al (2008) observed deformities in the bilateral symmetry of amphipods that inhabited beaches affected by greater tourist pressure. Human trampling and heavy tourist use are considered the main factors responsible for the direct or indirect mortality of T. saltator, considering that these activities can alter the degree of compacting of sediments and thus interfere with the movement of the organisms and consequently with their ability to escape (UGOLINI et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the morphological development of talitrid amphipods (T. saltator) have been associated with human impacts. On the coast of Spain, Barca-Bravo et al (2008) observed deformities in the bilateral symmetry of amphipods that inhabited beaches affected by greater tourist pressure. Human trampling and heavy tourist use are considered the main factors responsible for the direct or indirect mortality of T. saltator, considering that these activities can alter the degree of compacting of sediments and thus interfere with the movement of the organisms and consequently with their ability to escape (UGOLINI et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…La densidad de galerías de O. quadrata en las playas de la costa norte oriental fue, de forma general, menor que la encontrada por Turra et al (Araujo et al 2008), valores similares a los obtenidos en el presente estudio. En las costas de Estados Unidos se encontraron valores de densidad entre 0.005-0.014galerías/m 2 (Wolcott & Wolcott 1984), mientras Hobbs et al (2008) encontraron valores entre 0.02-0.13galerías/m 2 .…”
Section: Discussionunclassified
“…En playas de Brasil se han documentado aspectos relacionados con la distribución espacial de O. quadrata (Turra et al 2005, Neves & Bemvenuti 2006, Rosa & Borzone 2008, Araujo et al 2008) y con la variación espacio-temporal de su abundancia, así como la influencia de los depredadores sobre la estructura poblacional de la especie (Branco et al 2010). En México, se han realizado estudios sobre su abundancia y los patrones diarios de actividad (Valero-Pacheco et al 2007).…”
unclassified
See 2 more Smart Citations